2013
DOI: 10.1186/1471-2458-13-1217
|View full text |Cite
|
Sign up to set email alerts
|

Social and economic impact of diabetics in Bangladesh: protocol for a case–control study

Abstract: BackgroundDiabetes affects both individuals and their families and has an impact on economic and social development of a country. Information on the availability, cost, and quality of medical care for diabetes is mostly not available for many low- and middle-income countries including Bangladesh. Complications from diabetes, which can be devastating, could largely be prevented by wider use of several inexpensive generic medicines, simple tests and monitoring and can be a cost saving intervention. This study wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Prevalence of obesity is higher in urban areas as compared to the rural areas, since these are most affected by rapid changes in nutritional pattern and sedentary life style ( Shariful Islam et al , 2013). Rapid urbanization has been associated with a shift in labor force from agriculture to service sector which has reduced average physical activity status of the population.…”
Section: Drivers Of Nutrition and Dietary Transition And Their Impactmentioning
confidence: 99%
See 2 more Smart Citations
“…Prevalence of obesity is higher in urban areas as compared to the rural areas, since these are most affected by rapid changes in nutritional pattern and sedentary life style ( Shariful Islam et al , 2013). Rapid urbanization has been associated with a shift in labor force from agriculture to service sector which has reduced average physical activity status of the population.…”
Section: Drivers Of Nutrition and Dietary Transition And Their Impactmentioning
confidence: 99%
“…In 2000, 44% of the burden of disease in this region measured in disability adjusted life years (DALYs) was attributed to non-communicable diseases ( Basnyat & Rajapaksa, 2004). According to WHO guidelines for Asian populations, a third of the South Asian adult population is classified as obese, and 50% as overweight, by 2030 NCDs (T2DM, CVDs, COPD, cancer) and are going to account for 72% of total mortality by 2030 in South Asia ( Shariful Islam et al , 2013; Singh et al , 2011). In India, although under-nutrition and micronutrient deficiencies continue to be major public health problems, over-nutrition and obesity are also emerging as a major problem in many states(Kerala, Tamil Nadu).…”
Section: Epidemiological Transition In South Asia and The Burden Of Ncdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes is a serious disease that imposes heavy financial burden in affected individuals, their families and the nation at large [8, 9]. A recent study conducted on patients with type 2 diabetes attending an urban clinic in the capital city of Dhaka found that almost two-third of the patients had uncontrolled diabetes [10].…”
Section: Introductionmentioning
confidence: 99%
“…A study in Bangladesh demonstrated that around 90% of all diabetic patients did not check their sugar levels frequently had faced many clinical problems. 24 A study in Egypt showed that 38.6% of the patients had uncontrolled diabetes based on HbA1c levels with lower health-related QOL scores, 25 and a study in Oman showed that patients with less than 8% HbA1c levels showed a significant better QOL. 26 In our study, diabetic patients with complications showed a significantly lower score in the psychological domain.…”
Section: Methodsmentioning
confidence: 99%